Análisis del uso de ondas electromagnéticas en la irradiación del suelo para detectar y eliminar la presencia de nematodos - Poma Marín, Joan Sebastián (2016)
The plant-parasitic nematodes are responsible for heavy losses in agricultural production worldwide. This paper presents the analysis of an alternative control and detection of these microorganisms by use of electromagnetic waves. Was the experimental verification for the elimination, by the irradiation of magnetic field generated by an electromagnet fed by a pulsating variable current signal for various values of density of magnetic flux B. The mortality rate was observed at three values of magnetic flux density different to which resulted in a significant reduction in the number of nematodes against a sample control without radiation. For the detection of nematodes used algorithm of the finite-difference-domain (FDTD) weather led to a simulation in the MATLAB software, algorithm simulation allows to produce a certain incident wave that have contact with the micro-organism produces a variation in the amplitude of the radiated electric field wave which is reflected indicating the detection of the same two values of amplitude of incident wave was considered by checking the values of wave reflected for four micro-organisms with characteristics similar to the nematodes in different types of stadium.